Effect of Dietary Supplementation with Green Spirulina on the Survival Rate and Color Intensity of Goldfish (Carassius auratus) - Muhd. Rizky Marpaung; Dwi Tika Afriani; Bambang Hendra Siswoyo (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of adding natural carotenoid sources to feed on the enhancement of color intensity and survival rate of fish. The study employed a Completely Randomized Design (CRD) with four treatments and three replications, namely P1 (control), P2 (6% spirulina), P3 (8% spirulina), and P4 (10% spirulina). The experiment was conducted for 30 days using 60 experimental fish. The observed parameters included color intensity and survival rate. Data were analyzed using a one-way ANOVA. The results showed a significant difference among treatments on fish color intensity (P < 0.05). Treatment P3 (8% spirulina) produced the highest color intensity value (21.12 ± 0.27), followed by P4 (10%) (20.76 ± 0.19) and P2 (6%) (20.66 ± 0.07), while the lowest value was observed in P1 (control) (20.55 ± 0.14). However, no significant difference was found in the survival rate (P > 0.05), with the highest value in P1 (93%) and the other treatments showing similar values (87%). The addition of spirulina significantly improved fish color intensity, with the 8% dosage being the most effective treatment, but it did not significantly affect the survival rate.